2021
DOI: 10.1038/s41598-021-96938-9
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression as a predictor of postoperative recurrence and the association between the PD-L1 expression and EGFR mutations in NSCLC

Abstract: Although information on the PD-L1 expression and EGFR mutations in non-small cell lung cancer (NSCLC) is important for therapeutic strategies, the effect of these factors on postoperative recurrence and the association between each factor have remained unclear. We retrospectively assessed the PD-L1 expression and EGFR mutations in 280 NSCLC patients, and analyzed the associations by multivariate analyses. The hazard ratio (HR) of postoperative recurrence in cases with high (≥ 50%) PD-L1 expression regarding ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
4
14
0
1
Order By: Relevance
“…It is considered that the expression of PD-L1 in tumor cells is associated with a poor prognosis, as such lesions tend to show malignant tumor growth via immunosuppression. In fact, this theory has been supported by several studies [8,9], including our previous report [10]. However, since there are lung cancer patients with a high PD-L1 expression who have a good postoperative course in clinical practice, while other lung cancer patients with a low PD-L1 expression may show a poor postoperative course in clinical practice, the factors related to tumor immunity other than PD-L1 may also have a signi cant impact on the postoperative prognosis.…”
Section: Introductionsupporting
confidence: 78%
“…It is considered that the expression of PD-L1 in tumor cells is associated with a poor prognosis, as such lesions tend to show malignant tumor growth via immunosuppression. In fact, this theory has been supported by several studies [8,9], including our previous report [10]. However, since there are lung cancer patients with a high PD-L1 expression who have a good postoperative course in clinical practice, while other lung cancer patients with a low PD-L1 expression may show a poor postoperative course in clinical practice, the factors related to tumor immunity other than PD-L1 may also have a signi cant impact on the postoperative prognosis.…”
Section: Introductionsupporting
confidence: 78%
“…These results indicate the types of resistance mechanisms to EGFR-TKIs that promote the immune escape of tumor cells through different molecular mechanisms ( Figure 1 ). Based on these findings, several studies showed that PD-L1 expression levels as measured by immunohistochemistry (IHC) are relatively higher in advanced NSCLC with EGFR mutation or ALK fusion compared with that of NSCLC with wild-type EGFR and ALK , though the results of some studies were inconsistent [ 79 , 80 , 81 ].…”
Section: The Association Between Pd-l1 Expression and Efficacy Of Icis In Nsclc With Driver Gene Alterationsmentioning
confidence: 99%
“…The relationship between PD-L1 expression and EGFR mutations is controversial. In some reports, PD-L1 expression was signi cantly associated with wild-type EGFR whereas high PD-L1 expression (≥ 50%) was negatively associated with EGFR L858R mutation in exon 21 10,24 . Furthermore, several reports showed no association between PD-L1 expression and EGFR mutation 9,25,26 , whereas it was reported that PD-L1 expression was signi cantly associated with the presence of EGFR mutations 27 .…”
Section: Discussionmentioning
confidence: 98%
“…However, the prognostic relevance of PD-L1 expression in NSCLC is controversial. Although PD-L1 expression was revealed as a poor prognostic factor for NSCLC in several reports [6][7][8][9][10][11] , several studies demonstrated that PD-L1 expression is correlated with better prognosis 12,13 , while others have reported it as having no prognostic relevance 14,15 .…”
Section: Introductionmentioning
confidence: 99%